Antimicrobial studies of Ricinus communis seeds extracts (International Journal of Scientific Research and Management (IJSRM), 2015)
The bioactive molecules produced by medicinal plant react with microorganism and obstruct their growth and destroy their cells. Different polarity solvents were used for the extraction of Ricinus communis seeds. Antimicrobial activity of various Ricinus communis seeds extracts were screened against Rhodococcus spp, Bacillus subtilis, Escherichia coli, Aspergillus niger, Aspergillus flavus and Trichoderma harzianum. Chloroform and Methanol extracts showed maximum inhibition zone of bacterial and fungal strains, while Acetone extracts showed significant antifungal activity than antibacterial activity and n-Hexane extracts were found unable to show any significant antimicrobial activity.